2001
DOI: 10.1091/mbc.12.4.1019
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Transcytotic Machinery Involves Supramolecular Protein–Lipid Complexes

Abstract: We have demonstrated that the plasmalemmal vesicles (caveolae) of the continuous microvascular endothelium function as transcytotic vesicular carriers for protein molecules Ͼ20 Å and that transcytosis is an N-ethylmaleimide-sensitive factor (NSF)-dependent, N-ethylmaleimide-sensitive process. We have further investigated NSF interactions with endothelial proteins to find out 1) whether a complete set of fusion and targeting proteins is present in the endothelium; 2) whether they are organized in multimolecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 53 publications
5
81
1
Order By: Relevance
“…Morphological and biochemical studies demonstrated that in ECs, 25% of the entire amount of caveolin-1 is present in the cytosol. Cytosolic caveolin was found in a protein-lipid complex comprising general components of the membrane fusion-fission machinery (158). The finding is also consistent with a role of caveolin in cholesterol trafficking (46).…”
Section: Endothelial Caveolae: Specialized Vesicular Carriers With DIsupporting
confidence: 63%
See 2 more Smart Citations
“…Morphological and biochemical studies demonstrated that in ECs, 25% of the entire amount of caveolin-1 is present in the cytosol. Cytosolic caveolin was found in a protein-lipid complex comprising general components of the membrane fusion-fission machinery (158). The finding is also consistent with a role of caveolin in cholesterol trafficking (46).…”
Section: Endothelial Caveolae: Specialized Vesicular Carriers With DIsupporting
confidence: 63%
“…Caveolin-1 is also present, depending on the cell type, in the plasmalemma proper, mitochondria, and elements of the secretory pathway (96). Caveolin-1 can either be an integral membrane or a cytosolic soluble protein (96,156,158). As a soluble protein, caveolin-1 forms protein-lipid complexes containing cholesterol (158,217,238).…”
Section: Endothelial Caveolae: Specialized Vesicular Carriers With DImentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the relationship between dynamin and ensuing downstream signal transduction, which regulates the counterbalances of EC survival and apoptosis, may be significant. This is especially true in EC in which the dynamin-2 isoform is closely associated with key EC survival proteins, including the NO generating enzyme, endothelial NO synthase (eNOS), and the VEGF receptor, KDR (Bhattacharya et al, 2005;Chatterjee et al, 2003;Predescu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…2,3,7,11,12 The transport of macromolecules larger than 3 nm, such as albumin, IgG, and other macromolecules, occurs through the transcellular pathway, which is also called transcytosis or vesicular transport. 3,[12][13][14] Molecules smaller than 3 nm, such as glucose, water, and ions, can pass through interendothelial junctions (IEJs) through the paracellular pathway. 2,3,14 Both transcellular and paracellular pathways work in concert to maintain tissue-oncotic pressure and thereby maintain the endothelial barrier.…”
mentioning
confidence: 99%